Enhancing Speaking Abilities in Children With Speech Delays Through Role-Playing Interventions - Lavenia, Nia; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Speech delays affect approximately 5-10% of preschool children globally, with 7% of Indonesian children aged 4-5 years experiencing speech development difficulties. Role-playing methods have emerged as promising pedagogical approaches for addressing these challenges, yet systematic evidence for their effectiveness remains limited. This study aimed to investigate the effectiveness of role-playing methods in improving speaking abilities among children aged 4-5 years with speech delays. This classroom action research employed the Kemmis and McTaggart model across three cycles at TK Tunas Harapan 1, involving 13 children aged 4-5 years with speech delays. Each cycle consisted of planning, action, observation, and reflection phases with two meetings per cycle. Data collection utilized structured observation sheets, performance assessments with five-point rubric scales, interviews with teachers and parents, and documentation. Role-playing activities incorporated diverse themes including animal care, professional roles, transportation, and anti-bullying scenarios. Substantial improvements were observed across all implementation cycles. Average speaking scores increased from 42.41% (pre-intervention) to 68.99% (Cycle I), 82.85% (Cycle II), and 94.28% (Cycle III). Classical mastery rates improved from 7.69% to 92.30%, exceeding the 85% success criterion. All seven assessed speaking aspects showed significant enhancement: instruction comprehension, peer interaction responses, vocabulary usage, sentence construction, speaking confidence, expression and intonation, and conversational fluency. The findings validate role-playing effectiveness for speech delay intervention, supporting Vygotsky's sociocultural theory and Bandura's social learning theory. Results align with previous research while providing systematic implementation evidence across multiple cycles. The accessible, classroom-based approach offers practical implications for early childhood education settings addressing speech development challenges.